Actual Status of Law Application on Land Acquisition for Socio-Economic Development Purposes - Son , Cao Thanh (International Journal of Membrane Science and Technology, 2023)
Vietnamese law has regulations on land acquisition cases for socio-economic development for national and public benefits, limiting land acquisition cases according to the scale of each type of project that will be approved and deciding the investment and investment policy. However, certain realities still exist. Analysis and comparison are the main methods used in the study. The article aims to present the current situation and recommend improving the land acquisition law for socio-economic development.